2009
DOI: 10.1007/s12010-009-8733-6
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Naringinase in PVA–Alginate Matrix Using an Innovative Technique

Abstract: A synthetic polymer, polyvinyl alcohol (PVA), a cheap and nontoxic synthetic polymer to organism, has been ascribed for biocatalyst immobilization. In this work PVA-alginate beads were developed with thermal, mechanical, and chemical stability to high temperatures (<80 degrees C). The combination of alginate and bead treatment with sodium sulfate not only prevented agglomeration but produced beads of high gel strength and conferred enzyme protection from inactivation by boric acid. Naringinase from Penicillium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(88 citation statements)
references
References 48 publications
6
80
1
1
Order By: Relevance
“…It was also observed that high activity of the immobilized enzyme occurred in a broad pH between 5.2-6.4, which implied that the beads played a protective role for the immobilized enzyme. Similar results were reported for free phospholipase A1 in gelatin hydrogel (Sheelu et al, 2008), free naringinase in PVA matrices (Şekeroğlu et al, 2006;Nunes et al, 2010), laccase in PVA Cryogel Type Carrier (Stanescu et al, 2010) and dextranase in BSA with a cross-linking agent (El-Tanash et al, 2011).…”
Section: Effect Of Ph and Temperature On Enzyme Activitysupporting
confidence: 84%
See 3 more Smart Citations
“…It was also observed that high activity of the immobilized enzyme occurred in a broad pH between 5.2-6.4, which implied that the beads played a protective role for the immobilized enzyme. Similar results were reported for free phospholipase A1 in gelatin hydrogel (Sheelu et al, 2008), free naringinase in PVA matrices (Şekeroğlu et al, 2006;Nunes et al, 2010), laccase in PVA Cryogel Type Carrier (Stanescu et al, 2010) and dextranase in BSA with a cross-linking agent (El-Tanash et al, 2011).…”
Section: Effect Of Ph and Temperature On Enzyme Activitysupporting
confidence: 84%
“…Increasing the concentration of sodium alginate from 2% to 4%, the immobilized enzyme activity and immobilization yield decreased. The result suggest that the number of hydrogen bonds between polymer chains increased, which led to an increase in the density of physical cross-linking sites (Nunes et al, 2010;El-Din et al, 2007). Table 4 indicated the effects of different concentrations of phospholipase A1 immobilized in PVAalginate beads.…”
Section: The Effects Of Different Preparation Conditions Of Pva-alginmentioning
confidence: 98%
See 2 more Smart Citations
“…Naringinase activity was maintained for 15 days storage after preparation of the biocatalytic active packaging coating, and kM values were lower when compared to free enzyme. Nunes et al, achieved similar success by cross-linking naringinase to polyvinyl alcohol and alginate using boric acid for de-bittering [72]. In other work, β-galactosidase was bound to amine-functionalized polyethylene films by a dialdehyde tether to reduce milk lactose in package [64].…”
Section: Biocatalyticmentioning
confidence: 98%